On the quest of reliable 3D dynamic in vitro blood-brain barrier models using polymer hollow fiber membranes: Pitfalls, progress, and future perspectives - Mantecón-Oria, Marián; Rivero, María J.; Diban, Nazely; Urtiaga, Ane (Frontiers in Bioengineering and Biotechnology, 2022)
With the increasing concern of neurodegenerative diseases, the development of new therapies and effective pharmaceuticals targeted to central nervous system (CNS) illnesses is crucial for ensuring social and economic sustainability in an ageing world. Unfortunately, many promising treatments at the initial stages of the pharmaceutical development process, that is at the in vitro screening stages, do not finally show the expected results at the clinical level due to their inability to cross the human blood-brain barrier (BBB), highlighting the inefficiency of in vitro BBB models to recapitulate the real functionality of the human BBB. In the last decades research has focused on the development of in vitro BBB models from basic 2D monolayer cultures to 3D cell co-cultures employing different system configurations. Particularly, the use of polymeric hollow fiber membranes (HFs) as scaffolds plays a key role in perfusing 3D dynamic in vitro BBB (DIV-BBB) models. Their incorporation into a perfusion bioreactor system may potentially enhance the vascularization and oxygenation of 3D cell cultures improving cell communication and the exchange of nutrients and metabolites through the microporous membranes. The quest for developing a benchmark 3D dynamic in vitro blood brain barrier model requires the critical assessment of the different aspects that limits the technology. This article will focus on identifying the advantages and main limitations of the HFs in terms of polymer materials, microscopic porous morphology, and other practical issues that play an important role to adequately mimic the physiological environment and recapitulate BBB architecture. Based on this study, we consider that future strategic advances of this technology to become fully implemented as a gold standard DIV-BBB model will require the exploration of novel polymers and/or composite materials, and the optimization of the morphology of the membranes towards thinner HFs (< 50 μm) with higher porosities and surface pore sizes of 1-2 µm to facilitate the intercommunication via regulatory factors between the cell co-culture models of the BBB.